PENGGUNAAN MEDIA SCRAPBOOK PADA KETERAMPILAN MENULIS DESKRIPSI SISWA KELAS IV MADRASAH IBTIDAIYAH - auliya, arizatul; oktaviani, rizka; jihan, alvin; adelia, cindy; sari, benedikta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Writing skills are very important for students' personal development, it seems that fourth grade students do not enjoy teaching writing skills. Fourth grade students face problems in the use of punctuation marks and capital letters. This study aims to determine whether scrapbooks are a learning tool that might be of interest to fourth grade students. This research examines the use of scrapbooks on the writing skills of MI Haji Hasyim students, how their writing skills develop after using scrapbooks, the obstacles teachers face in carrying out learning, and the advantages of scrapbooks, namely helping students learn new vocabulary through games. This type of descriptive qualitative research was used in this research to explain how effective the use of Scrapbook media is on students' writing abilities in the fourth grade of elementary school. Data collection was carried out through observation, documentation and interviews. In their data analysis, researchers used the Miles and Huberman model to analyze their data, reduce it, describe it, and draw conclusions. Qualitative data is analyzed in stages until it becomes complete data. The research results show that teachers must update the activities to be carried out and issue scrapbook media based on the results of students' LKPD in class IV. Of the 23 students, there are some who are not yet skilled in writing. Teachers also face problems due to lack of attention and encouragement of students' interest in learning. Apart from that, students are less fluent in reading and writing at the previous level.